Integrated Modules Analysis to Explore the Molecular Mechanisms of Phlegm-Stasis Cementation Syndrome with Ischemic Heart Disease - Xu, Wei-Ming; Yang, Kuo; Jiang, Li-Jie; Hu, Jing-Qing; Zhou, Xue-Zhong (Frontiers in Physiology, 2018)
Background Ischemic heart disease (IHD) has been the leading cause of death for several decades, IHD patients usually hold the symptoms of phlegm-stasis cementation syndrome (PSCS) as significant complications. However, the underlying molecular mechanisms of PSCS complicated with IHD were not fully elucidated. Materials and Methods We utilized network medicine methods to elucidate the underlying molecular mechanisms of IHD phenotypes. Firstly, we integrated high-quality IHD-associated genes from both human curated disease-gene association database and biomedical literatures. Secondly, we obtained the IHD disease modules by dissecting the protein-protein interaction (PPI) topological modules in the String V9.1 database and the mapping of IHD-associated genes to the PPI topological modules. After that, we carried out molecular functional analyses (e.g. Gene Ontology and pathway enrichment analyses) for these IHD disease modules. Finally, we identified the PSCS syndrome modules by mapping the PSCS related symptom-genes to the IHD disease modules, which were further validated by both pharmacological and physiological evidences derived from published literatures. Results We integrated and evaluated 1,056 high-quality IHD-associated genes. In addition, we identified eight IHD disease modules (the PPI sub-networks significantly relevant to IHD), in which two disease modules were relevant to PSCS syndrome (i.e. two PSCS syndrome modules). These two modules had enriched pathways on Toll-like receptor signaling pathway (hsa04620) and Renin-angiotensin system (hsa04614), with the molecular functions of angiotensin maturation (GO:0002003) and response to bacterium (GO:0009617), which had been validated by classical Chinese herbal formulas-related targets, IHD-related drug targets, and the phenotype features derived from human phenotype ontology (HPO) and published biomedical literatures. Conclusion We proposed a network medicine-based approach to identify the underlying molecular modules of PSCS complicated with IHD, which could be used for interpreting the pharmacological mechanisms of well-established Chinese herbal formulas (e.g. Tao Hong Si Wu Tang, Dan Shen Yin, Hunag Lian Wen Dan Tang and Gua Lou Xie Bai Ban Xia Tang). In addition, our results delivered novel understandings of the molecular network mechanisms of IHD phenotype subtypes with PSCS complications, which would be both insightful for IHD precision medicine and the integration of disease and TCM syndrome diagnoses.